2000
DOI: 10.1111/j.1095-8649.2000.tb00875.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different initial size distributions on the growth of Atlantic halibut

Abstract: Growth rate of individually tagged medium-sized (249 6·9 g) juvenile halibut was 18% lower when medium sized fish were reared alone (treatment Mm) as compared with rearing with either large/dominant (382 12·1 g) (Ml) or small/subordinate (158 3·1 g) (Ms) conspecifics. The coefficient of variation of weight of medium-sized fish increased with weight in both the Mm and the Ml group whereas it was stable in the Ms group. Size rank correlation between initial and final weight was highest in the Mm group and lowest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 46 publications
2
19
0
1
Order By: Relevance
“…; y p À Á for each p (age) measurement on n individual fish; X(n 9 q) is the design matrix or the set of extraneous variables measured for each individual, i.e., q = age p + grading group i + replicate j ; (i = Control, LS, SS, LL and SL), (k = replicate a, replicate b); B(q 9 p) is the matrix of parameters estimated by the model; and E(n 9 p) is the matrix of deviations for each individual from the expected value of Y = XB. Two-way nested ANOVA (Searle et al 1992), where the two replicates were nested within experimental groups, was used to calculate the effect of different social environments on mean weights and specific growth rates. The model equation of the nested ANOVA had the form:…”
Section: Data Analysis and Statistical Methodsmentioning
confidence: 99%
“…; y p À Á for each p (age) measurement on n individual fish; X(n 9 q) is the design matrix or the set of extraneous variables measured for each individual, i.e., q = age p + grading group i + replicate j ; (i = Control, LS, SS, LL and SL), (k = replicate a, replicate b); B(q 9 p) is the matrix of parameters estimated by the model; and E(n 9 p) is the matrix of deviations for each individual from the expected value of Y = XB. Two-way nested ANOVA (Searle et al 1992), where the two replicates were nested within experimental groups, was used to calculate the effect of different social environments on mean weights and specific growth rates. The model equation of the nested ANOVA had the form:…”
Section: Data Analysis and Statistical Methodsmentioning
confidence: 99%
“…Criações em tanques-rede de pequeno volume podem ser mais vantajosas que as criações tradicionais, uma vez que permitem altas densidades de estocagem e, quando ideais, podem quebrar o status social de dominância e subordinação (Alanärä & Brännäs, 1996), tendendo à manutenção de lotes mais homogêneos (Trzebiatowski et al, 1981;Teskeredzic et al, 1986) e, conseqüentemente, aumentando a produtividade (Hengsawat et al, 1997). A estocagem de lotes de peixes com tamanhos homogêneos iniciais influenciam na homogeneidade do lote final (Stefansson et al, 2000).…”
Section: Introductionunclassified
“…They hypothesized that fish competition was very high just after size grading, and decreased with time. In some species, size grading might lead to the destruction of size hierarchy, the growth of the large fish being adversely affected by the stronger agonistic interaction, and intraspecific aggression occur among the graded large individuals (Baardvik and Jobling 1990;Stefánsson et al 2000;Sunde et al 1998). In sea bass, no studies have reported a high level of aggression under self-feeding conditions, as the reward level after each trigger actuation usually optimizes feed allocation to the group.…”
Section: The Effects Of a Reduction In The Body Weight Coefficient Ofmentioning
confidence: 99%
“…Some experiments supported the usefulness of grading procedures based on asymmetric competition (abalone, Haliotis tuberculata, Mgaya and Mercer 1995), while others reported either lower growth rates in graded fish (cod, Gadus morhua (Lambert and Dutil 2001) or no biomass gain: Arctic charr, Salvelinus alpinus (Wallace and Kolbeinshavn 1988;Baardvik and Jobling 1990); Atlantic salmon, Salmo salar (Gunnes 1976); eel, Anguilla anguilla (Kamstra 1993); Dover sole, Solea solea L. (Overton et al 2010). In some species, destruction of size hierarchies does improve the growth of the small fish but the growth of the large fish could be adversely affected by the stronger agonistic interaction and intraspecific aggression occurring among the graded large individuals (Baardvik and Jobling 1990;Sunde et al 1998;Stefánsson et al 2000). Furthermore, size grading is in itself a stressful procedure for fish (Pickering 1981) and is labour-intensive, with risks of handling damage, disease outbreak, and growth reduction (Sunde et al 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation